Faktor-faktor yang Mempengaruhi Praktik Perataan Laba pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Rahayu Dahliawati; La Ane (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2017)
Company valuation in general becomes one of the goals of Income Smoothing practice. The purpose of this research is to examine thein fluence of Sales  Growth,  Return On Asset,  Debt  to  Asset  Ratio, as  well  as  to examine whether there is influence on Earning Response(CAR).The population in this researchare Manufacturing Company of Basic and Chemical Industry Sector listed on Indonesia Stock Exchange which totals 64 companies. Sample consist of 31 manufacturing company of the Basic and Chemical Industry Sectors listed on the Indonesian Stock Exchange for 5 years from 2011–2015, with subsamples of 155 financial statement. The technique of selecting samples using Purposive Sampling technique. Data analysis technique used is descriptive statistic, normalitytest, testclassic assumptions, hypothesis test (T test statistic, F-Test and path analysis).There sults showed that: First, Sales Growth, Return On Asset, and Debt toAsset Ratio variabel do not have a significant effecton Income Smoothing Practice. This means that all of these variables are not able to detect management behavior in the Income Smoothing Practice. Second, Sales Growth, Return On Assetand Debtto Asset Ratio variables do not have a directinfluence on Earning Response. This means that investors in the capital market have not considered these variable factors in making  investment decisions. Third, Sales Growth, Return On Assetand Debt to Asset Ratio variables have no effecton Earning Response even though through Income Smoothing Practice. This means that investors in decision making through considerate on of Income Smoothing by management also does not consider factor variable.The conclusion that can be drawn from there sults of this researchis by knowing the influence of these variables, investors can choose a strategy  to choosea company that is really considered healthy as a place to invest. Keywords :     Income Smoothing, Sales Growth, Return on Asset, Debtto Asset Ratio, Earning Response (CAR).